Noise source imaging measurements for small-scale multi-propeller systems. (15th June 2022) - Zhou, Teng; Jiang, Hanbo; Sun, Xiangyu
Highlights: Identification of the interactional noise source in the gap between two side-by-side placed propellers. Noise source imaging on a realistic hovering drone inside a large anechoic chamber using a 8 × 9 microphone array on the ground. Abstract: Noise source features of multi-propeller systems are experimentally studied in this paper. Noise sources on a pair of side-by-side placed small-scale propellers and a flying quad-copter are investigated separately using microphone arrays and the conventional beamforming algorithm. A high-intensity noise source spot is identified within the gap area between two propeller disks, which is a result of the interaction between the blade tip and upwash flow within the gap area. As the two propellers move away from each other, the noise source spot becomes weaker. Similarly, for a quad-copter under realistic flight conditions, the strongest noise sources are observed within the gap between each of two adjacent propellers, showing the feasibility and repeatability of the result obtained in the lab. The results discussed in this paper show that for the low-noise design of a multi-propeller drone, not only is the single propeller noise, but also the propeller interactional noise shall be taken into account.